1994
DOI: 10.1136/ard.53.5.338
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic hypertrophic osteoarthropathy and liver transplantation.

Abstract: Objectives-To document the variety of liver diseases and the clinical picture of hepatic hypertrophic osteoarthropathy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 6 publications
1
9
0
Order By: Relevance
“…Hypertrophic osteoarthropathy can be a painful syndrome of arthritis and joint deformities that has been observed in chronic liver disease, including biliary atresia 118, 119. In some circumstances, it has been responsive to standard anti‐inflammatory treatments.…”
Section: Hypertrophic Osteoarthopathymentioning
confidence: 99%
“…Hypertrophic osteoarthropathy can be a painful syndrome of arthritis and joint deformities that has been observed in chronic liver disease, including biliary atresia 118, 119. In some circumstances, it has been responsive to standard anti‐inflammatory treatments.…”
Section: Hypertrophic Osteoarthopathymentioning
confidence: 99%
“…In addition to juvenile polypo- sis, previous reports described PDP associated with other hamartomatous disorders, such as cystic fibrosis in the lung or liver. 13,19 Juvenile polyposis is often observed in the colon, but it is relatively rare in the stomach and the small bowel. Watanabe et al 20 reported a rare case of juvenile polyposis limited to the stomach.…”
Section: Discussionmentioning
confidence: 99%
“…Hypertrophic osteoarthropathy with associated arthritis was described in patients with hepatic failure and transplantation (23). It has been emphasized that when HOA occurs in the setting of liver disease it usually heralds a worsening of hepatic function (6). The pathogenesis of HOA is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Osteoarthritic changes due to osteopenia and rheumatic complications were also reported following transplantation (5). Hepatic hypertrophic osteoarthropathy (HOA) has been documented in case reports (6,7,8,9,10). In addition to metabolic bone disease, metastatic bone disease was encountered following long periods of cirrhosis giving rise to the high incidence of hepatocellular carcinoma (HCC) (11,12).…”
Section: Introductionmentioning
confidence: 99%